The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1159/000345056
|View full text |Cite
|
Sign up to set email alerts
|

Micropercutaneous Nephrolithotomy (Microperc) in a Two-Year-Old with the ‘All-Seeing Needle'

Abstract: This paper presents the use of the single-step micropercutaneous nephrolithotomy (microperc) procedure for the treatment of a 13-mm renal stone using a 4.85-Fr ‘all-seeing needle' in a 2-year-old toddler. In the current literature to date, this is the youngest case. Moreover, the advantages and reliability of this technique in toddler renal stone treatment are also evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…[20] RIRS is associated with a small but significant risk of injury to the delicate pediatric ureters. [21] In a series of 170 children undergoing flexible ureteroscopy, 57% required passive dilatation of the ureter for 1-2 weeks before ureteroscope could be inserted into the ureter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] RIRS is associated with a small but significant risk of injury to the delicate pediatric ureters. [21] In a series of 170 children undergoing flexible ureteroscopy, 57% required passive dilatation of the ureter for 1-2 weeks before ureteroscope could be inserted into the ureter.…”
Section: Introductionmentioning
confidence: 99%
“…[102029] Since this procedure is still in its early stages of development, there are no large series or prospective studies in the pediatric age group. In pre-school children, 14 G angiocath can be used similar to amplatz sheath in PCNL.…”
Section: Introductionmentioning
confidence: 99%
“…The microperc procedure, which is performed through a smaller tract, has led to lesser parenchymal and vascular damage within narrow infundibula, and calyces resistant to dilatation [3,4]. Kaynar et al [8] shared the results of the microperc procedure they performed for the treatment of a 2-year-old infant with a renal stone. The authors reported that the microperc technique was a safe and efficient procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney stones can be treated in a variety of ways and percutaneous nephrolithotomy (PNL) has been a very important part of this treatment modalities since it was first introduced in 1976 [ 1 ].…”
Section: Introductionmentioning
confidence: 99%